Cell Surface Expression of Endosomal Toll-Like Receptors—A Necessity or a Superfluous Duplication? - Mielcarska, Matylda Barbara; Bossowska-Nowicka, Magdalena; Toka, Felix Ngosa (Frontiers in Immunology, 2021)
Timely and precise delivery of the endosomal Toll-like receptors (TLRs) to the ligand recognition site is a critical event in mounting an effective antimicrobial immune response, however, the same TLRs should maintain the delicate balance of avoiding recognition of self-nucleic acids. Such sensing is widely known to start from endosomal compartments, but recently enough evidence has accumulated supporting the idea that TLR-mediated signaling pathways originating in the cell membrane may be engaged in various cells due to differential expression and distribution of the endosomal TLRs. Therefore, the presence of endosomal TLRs on the cell surface could benefit the host responses in certain cell types and/or organs. Although not fully understood why, TLR3, TLR7, and TLR9 may occur both in the cell membrane and intracellularly, and it seems that activation of the immune response can be initiated concurrently from these two sites in the cell. Furthermore, various forms of endosomal TLRs may be transported to the cell membrane, indicating that this may be a normal process orchestrated by cysteine proteases – cathepsins. Among the endosomal TLRs, TLR3 belongs to the evolutionary distinct group and engages a different protein adapter in the signaling cascade. The differently glycosylated forms of TLR3 are transported by UNC93B1 to the cell membrane, unlike TLR7, TLR8 and TLR9. The aim of this review is to reconcile various views on the cell surface positioning of endosomal TLRs and add perspective to the implication of such receptor localization on their function, with special attention to TLR3. Cell membrane-localized TLR3, TLR7, and TLR9 may contribute to endosomal TLR-mediated inflammatory signaling pathways. Dissecting this signaling axis may serve to better understand mechanisms influencing endosomal TLR-mediated inflammation, thus determine whether it is a necessity for immune response or simply a circumstantial superfluous duplication, with other consequences on immune response.